2001
DOI: 10.1161/hh2301.100250
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Calcium Sparks and Spontaneous Transient Outward Currents by RyR3 in Arterial Vascular Smooth Muscle Cells

Abstract: Abstract-Intracellular

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
80
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(84 citation statements)
references
References 39 publications
2
80
2
Order By: Relevance
“…The role of RyR2 in Ca 2ϩ spark signaling has been extensively studied in the heart, but we know the least about the role of RyR3 in the generation of Ca 2ϩ sparks in SMCs. RyR3 gene knockout or knockdown does not alter local Ca 2ϩ signaling in bladder and portal vein SMCs (8,17); yet, it has been reported that the frequency of STOCs is augmented in RyR3 Ϫ/Ϫ cerebral artery myocytes (27). This result has been interpreted as evidence for the inhibitory role of RyR3 in the development of Ca 2ϩ sparks, since STOCs are generally thought to be activated by Ca 2ϩ sparks.…”
Section: Discussionmentioning
confidence: 99%
“…The role of RyR2 in Ca 2ϩ spark signaling has been extensively studied in the heart, but we know the least about the role of RyR3 in the generation of Ca 2ϩ sparks in SMCs. RyR3 gene knockout or knockdown does not alter local Ca 2ϩ signaling in bladder and portal vein SMCs (8,17); yet, it has been reported that the frequency of STOCs is augmented in RyR3 Ϫ/Ϫ cerebral artery myocytes (27). This result has been interpreted as evidence for the inhibitory role of RyR3 in the development of Ca 2ϩ sparks, since STOCs are generally thought to be activated by Ca 2ϩ sparks.…”
Section: Discussionmentioning
confidence: 99%
“…Functional Ca 2ϩ release units comprised of multiple RyR isoforms have also been implicated in cerebral artery smooth muscle cells. It was reported that the frequency of Ca 2ϩ sparks and spontaneous transient outward currents in cerebral artery smooth muscle cells isolated from RyR3-deficent mice was significantly higher than that in wild type cells (15). These data suggest that RyR3 is part of the functional Ca 2ϩ release units formed by RyR2 or RyR1 and regulates their activity negatively.…”
Section: Discussionmentioning
confidence: 87%
“…The observation that abolition of RyR3 increases the frequency of Ca 2ϩ sparks in smooth muscles suggests that RyR3 may normally inhibit the activity of Ca 2ϩ release units (15). RyR3 expressed in smooth muscle appears to function differently from that expressed in skeletal muscle.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ca 2+ sparks) that result from the opening of tightly clustered ryanodine receptor channels located at extensions of sarcoplasmic reticulum. Ca 2+ sparks activate a BK Ca -dependent hyperpolarizing current that opposes the smooth muscle depolarization, and thereby, regulates the magnitude of the vasoconstriction (Jaggar et al, 1998;Gollasch et al, 2000;Gordienko et al, 2001;Lohn et al, 2001). SK Ca and IK Ca channels play a central role in the endothelial cell control of vasomotor tone and peripheral vascular resistance (Busse et al, 2002;Eichler et al, 2003;Taylor et al, 2003;Si et al, 2006;Brahler et al, 2009).…”
Section: Membrane Potential and Vascular K + Channelsmentioning
confidence: 99%